Factors associated with disease-specific quality of life in Taiwanese patients with ankylosing spondylitis: a cross-sectional study - Lu, Ming-Chi (BMJ Open, 2019)
OBJECTIVE: The aim of this study was to assess the factors associated with disease-specific quality of life in Taiwanese patients with ankylosing spondylitis. DESIGN: A cross-sectional study. SETTING: A regional teaching hospital in southern Taiwan. PARTICIPANTS: Adult patients with ankylosing spondylitis recruited from the outpatient rheumatology clinics of the study hospital. PRIMARY OUTCOME MEASURE: Disease-specific quality of life assessed by the Evaluation of Ankylosing Spondylitis Quality of Life (EASi-QoL). RESULTS: Of the 265 patients, 57% were 20–49 years of age, with a male preponderance (75.5%). Multiple stepwise linear regression analysis indicated that a higher disease activity, assessed by the Ankylosing Spondylitis Disease Activity Score, was significantly and independently associated with a lower quality of life in all four domains (physical function, disease activity, emotional well-being and social participation) of the EASi-QoL. In addition, various independent factors, including educational level, nature of occupation, disease duration, dietary habit and body mass index, were significantly associated with different domains of the EASi-QoL. CONCLUSIONS: Our findings indicated that, in addition to disease activity and perceived health status, a number of other factors could significantly impact the different aspects of quality of life in patients with ankylosing spondylitis, which warrant special consideration and support from healthcare providers.